Developing Website-based Interactive Learning Media Integrated with Kirchhoff's Law Experimental Tools - Fani Mardianti; Dian Purnama; Siti Zaenab; Dadi Rusdiana (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
Understanding the correct concept is a fundamental goal of learning physics. One material that is still vulnerable to conceptual understanding is Kirchhoff's law. For that, we need media that can bridge the understanding of the concept of this material. Media development by integrating real experimental tools with digital technology is the right solution to answer this problem. Integrated interactive Google site with tool practice form senior high school tool simplification designed for upgrade understanding concept science high school students on the material Kirchhoff's law electricity dynamic. Development used R&D with 4D stages (Define, Design, Development, Disseminate). Media implementation used limited tests with some students and implementation through one class in a high school in Bandung. Data analysis used the Rasch model. Based on the results of Rasch Model analysis, students tested have a medium category, and the given predictions in the Google Sites were high and low. Based on the analysis results of student responses to tools, students who used the tool directly agreed and strongly agreed that it and Google Sites could improve their conceptual comprehension skills.